La copie de l'hymne à Asclépios d'Apollonia d'Illyrie (SEG 65 397). - Alonso Déniz, Alcorac (Mnemosyne, 2022)
A lead tablet from Apollonia in Illyria exhibits the last strophe of a paean to Asclepios, that is transmitted in its entirety on inscriptions from four other cities. This article presents some alternative readings of the new fragmentary version and analyses its variants through the prism of the interaction between the local dialect of the Corinthian colony and the literary Doric of traditional choral lyric. Moreover, some linguistic discrepancies between the different versions of the hymn may have been conditioned by specific local characteristics of religious songs.